The Hunger Games spectacle, risk and the girl action hero - Driscoll, Catherine; Heatwole, Alexandra (Routledge, Taylor & Francis Group, 2020)
The 2012 film The Hunger Games and its three sequels, appearing quickly over the following three years, represent one of the most successful examples of the contemporary popularity of youth-oriented speculative film and television series. This book considers "The Hunger Games" as an intertextual field centred on this blockbuster film franchise but also encompassing the successful novels that preceded them and the merchandised imagery and the critical and fan discourse that surrounds them. It explores the place of The Hunger Games in the history of youth-oriented cinema; in the history of speculative fiction centred on adolescents; in a network of continually evolving and tightly connected popular genres; and in the popular history of changing ideas about girlhood from which a successful action hero like Katniss Everdeen could emerge
Keywords: Collins, Suzanne -- 1962- -- The hunger games; bicssc / Media studies; bicssc / Sociology; bicssc / Film theory & criticism; bicssc / Popular culture